2020
DOI: 10.3390/md18070364
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Cyclic and Acyclic B-Type Laxaphycins in SH-SY5Y Human Neuroblastoma Cells

Abstract: Laxaphycins are a family of non-ribosomal lipopeptides that have been isolated from several cyanobacteria. Some of these compounds have presented cytotoxic activities, but their mechanism of action is poorly understood. In this work, the already described laxaphycins B and B3, and acyclolaxaphycins B and B3 were isolated from the marine cyanobacteria Anabaena torulosa. Moreover, two new acyclic compounds, [des-(Ala4-Hle5)] acyclolaxaphycins B and B3, were purified from the herviborous gastropod Stylocheilus st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 53 publications
(92 reference statements)
0
34
0
Order By: Relevance
“…SH-SY5Y cells were seeded into 96-well plates at a density of 5 × 10 4 cells per well and allowed to grow for 24 h. Cells were treated with compounds 1 and 2 at different concentrations (0.01, 0.1, 0.5, 1, 2.5, 5, 7.5, and 10 μM) for 6 and 24 h. The cytotoxic effect of compounds was evaluated with MTT (3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay [ 54 , 55 , 56 ]. SH-SY5Y cells were rinsed with saline solution and 200 μL of 500 μg/mL MTT (Merck, Darmstadt, Germany) dissolved in saline buffer were added to each well.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…SH-SY5Y cells were seeded into 96-well plates at a density of 5 × 10 4 cells per well and allowed to grow for 24 h. Cells were treated with compounds 1 and 2 at different concentrations (0.01, 0.1, 0.5, 1, 2.5, 5, 7.5, and 10 μM) for 6 and 24 h. The cytotoxic effect of compounds was evaluated with MTT (3-(4,5-dimethyl thiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay [ 54 , 55 , 56 ]. SH-SY5Y cells were rinsed with saline solution and 200 μL of 500 μg/mL MTT (Merck, Darmstadt, Germany) dissolved in saline buffer were added to each well.…”
Section: Methodsmentioning
confidence: 99%
“…The cell death type induced by compounds was determined with an Annexin V-FITC Apoptosis detection kit (Immunostep, Salamanca, Spain) following the manufacturer’s instructions [ 56 ]. Cells were seeded in 12-well plates at 1 × 10 6 cells per well and treated with compounds at IC 50 concentrations for 6 and 24 h. Then, cells were washed, resuspended in PBS (Phophate-Buffered Saline), and 5 μL of Annexin V-FITC and Propidium Iodide (PI) were added to each tube.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alvariño et al have reported the isolation of four acyclic peptides— acyclolaxaphycin B and acyclolaxaphycin B3 (originally found in the marine cyanobacteria Anabaena torulosa [ 125 ]), as well as [des-(Ala 4 -Hle 5 )]acyclolaxaphycin B and [des-(Ala 4 -Hle 5 )]acyclolaxaphycin B3 —from herbivorous gastropod Stylocheilus striatus [ 126 ]. The authors examined their activity in human neuroblastoma SH-SY5Y cells.…”
Section: Marine Compounds With a Non-validated Autophagy-modulatormentioning
confidence: 99%